PENGARUH PERCEIVED USEFULNESS, EASE OF USE, SECURITY, DAN PROMOTION TERHADAP CUSTOMER SATISFATION MOBILE PAYMENT APLIKASI OVO DI KOTA PONTIANAK - Bernardinus, Bernardinus B1021161104 (Jurnal Manajemen Update, 2021)
ABSTRACTThis study aims to determine the effect of Perceived Usefulness, Ease of Use, Security, and Promotion on Customer Satisfaction Mobile Payment OVO Applications in Pontianak City. The subjects in this study were users of the Ovo application service in the Pontianak City area. The type of data in this study is the type of primary data. The sample used in this study amounted to 100 respondents. The method used in determining the sampling is using purposive sampling. The technique of collecting and obtaining research data uses a survey technique, namely a questionnaire. The data analysis method used in this research is multiple linear analysisBased on the analysis that has been carried out, the results show that the Effect of Ease of Use, Security, and Promotion has a significant effect on Customer Satisfation Mobile Payment for the OVO application, while Perceived Usefulness and Promotion have no effect on Customer Satisfation Mobile Payment for the OVO application. Keywords: Perceived Usefulness, Ease of Use, Security, Promotion and Customer SatisfactionDAFTAR PUSTAKA Abidin, M. (2015). Dampak Kebijakan e-Money di Indonesia Sebagai Alat   Sistem. Surabaya: Universitas Negeri Surabaya.Aritonang, Y. A. (2017 ). Pengaruh Persepsi Kemudahan Dan persepsi manfaat terhadap  E-money. Jurnal Akuntansi STIE Multi Data Palembang, 1-17.Aeni, A. N., dan Purwantini, A. H. (2017). Eksplorasi Penggunaan Mobile Banking: Pendekatan Technology Model. Jurnal Analisis Bisnis Ekonomi, 15(1), 86 - 96Azwar, S. (2013). Reliabilitas dan Validitas. Yogyakarta: Pustaka Pelajar.Chin, W. T. (1995). On the use, usefulness and ease of use of structural equation modeling in MIS research. MIS Quarterly, 237-246Davis,F. D. (1986). Technology Acceptance Model for Empirically Testing New End – User Information System Theory and Results, Unpublished Doctoral Dissertation MIT.Davis, F. D. (1989). Perceived Usefulness, Perceived Ease of Use, and Acceptance of Information System Technology. Management Information Systems Quartely, 319-339Djaslim, Saladin. (2003). Manajemen Pemasaran Analisis, Perencanaan, Pelaksanaan, dan Pengendalian. Bandung: Linda KaryaDewi, N. M., dan Warmika., I. G. (2016). Peran Persepsi Kemudahan, Persepsi Manfaat dan Persepsi Resiko Terhadap Niat Menggunakan Mobile Commerce di Kota Denpasar. E-Jurnal Manajemen Unud, Voc:5,no.4Ghozali, I. ( 2011). Aplikasi Analisis Multivariate dengan IBM SPSS 19. Edisi Kelima. Universitas Diponegoro. Semarang.Hendra, J., dan Iskandar., R. A. (2016). Aplikasi Model TAM Terhadap Pengguna Layanan Internet Banking di Kantor Bank Jatim Cabang Situbondo. Jurnal Ilmiah Ecobuss, 4(1), 40 - 48.Hoque & Sorwar (2017). Understanding Factors Influencing the Adoption of mHealth by the Elderly: An Extention of the UTAUT Model. International Journal of Advanced Computer Science and Applications(IJACSA). Vol 9.Jogiyanto. (2007). Sistem Informasi Keprilakuan. Yogjakarta: AndiKotler, dan Amstrong. (2008). Prinsip prinsip pemasaran jilid 1 dan 2 edisi 12. Jakarta; Erlangga  Kotler, P. (2012). Manajemen Pemasaran di Indonesia: perencanaan, Implementasi dan pengendalian. Jakarta; penerbit Salemba, 4Kotler, P dan Keller, K. L. (2007). Manajemen Pemasaran edisi 12. Jilid 2. Jakarta; PT.IndeksKotler,P dan Keller, K. L. (2008). Manajemen Pemasaran edisi 13 Jilid 1. Jakarta; ErlanggaKotler, P dan Keller, K. L. (2009). Manajemen Pemasaran edisi 13. Judul 1. Jakarta; ErlanggaKotler, P dan Keller, K. L. (2011). Manajemen Pemasaran edisi 13 Jilid 1 dan 2, Ahli Bahasa : Bob Sabran. Jakarta; ErlanggaKarim, M. A. (2017). Pengaruh Penerimaan Sistem Pembayaran GO-Jek mengunakan TAM ( Technology Acceptance Model) terhadap intensitas pengunaan layanan Go-Jek. Skripsi. Fakultas Ekonomi Universitas Islam Indonesia: YogjakartaKarnouskos. (2004). Mobile Payment: A Journey Through Existing Procedures and Standardization Initiatives. IEEE Communications Survey and Tutorials. 6(4): 44 - 66Lee, C., dan Wan, G. (2010). Including subjective norm and technology trust in the technology acceptance model. ACM SIGMIS Database Lallmahomood., M. (2007). An Examination of Individuals Perceived Security and the Influnce of This On Their Intention To Use E-Commerce: Using An Extension of the Technology Acceptance Model . Journal of Internet Banking and Commerce. 12(3): 1 - 26Latifah, dan AZka, A. N. (2013). Pengaruh Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment dan Attitude Terhadap Pemanfaatan Visual Hotel Program pada Hotel - Hotel di Jogjakarta. Volume 4(1): 33 - 47Pikkarainen, et al. (2004). Consumer Acceptance of Online banking: An Extension of Technology Model Internet Research. Volume 14(3): 224 - 235Ryu dan Murdock. (2013). Customer Acceptance of Mobile Marketing Comunications Using QR Code. Texas State University : Journal of Marketing 111 -114Surendran, (2012). Technology Acceptance Model : A Survey of Literature. International Journal of Business and Research (IJBSR), 2(4), 175 - 178Sugiono, (2012). Memahami Penelitian Kuantitatif. Bandung; AlfabetaSiregar,. S. (2013). Metode Penlitian Kuantitatif. Jakarta: PT. Fajar Interpertama Mandiri.Untoro, R. Aria, T dan Komala, D. (2013). Pemetaan Produk dan Risiko pembayaran bergerak Mobile Payment dalam sistem pembayaran di Indonesia. Working Paper. No.2. Bank IndoensiaVenkatesh, V dan Davis, F. D, (2000). A Theoretical Extension Of The Thecnology Acceptance Model: Four Longitudinal Field Studies. Management Science, 46 (2), PP: 186-204Venkatesh, V., Morris, M. G., dan Davis, F. D. (2003). User Acceptance of Information Technology: Toward a Unified View. MIS Quarterly, Vol. 27 No. 3, PP. 425 - 478Wentker., D. Erick., K. Gavin., S. dan Doug., D. (2014). Mobile Payment Management. US Grants. US8923827B2. google PatentsYusuf,. M. (2014). Metode Penelitian Kuantitatif, Kualitatif, dan Penelitian Gabungan. Jakarta: Prendamedia Group.Zahid, N . Mujtaba, A dan Riaz, A. (2010). Customer Accptance of Online Banking. European Journal of Economic, 27(27: 44.